The role of hydrogen in the nitriding of anatase TiO 2 films in the N 2 -H 2 microwave afterglows - Ryu, Seol; Wang, Yunfei; Ricard, Andre; Sarrette, Jean Philippe; Kim, Ansoon; Kim, Yu Kwon (Surface and Coatings Technology, 2019)
Nitriding in the afterglows can be beneficial in the surface-selective nitridation of oxide materials for the control of surface defects or active sites in electronic devices or catalysts. Here we introduce our results on the nitriding of anatase TiO 2 films in the afterglows of N 2 -H 2 microwave plasmas at the substrate temperatures up to 300 °C. We employed optical emission spectroscopy (OES) and X-ray photoemission spectroscopy (XPS) to determine active species in the afterglows and the N species incorporated into the film, respectively. Adding a few percent of H 2 into the N 2 gas flow generates active species such as NH and H atoms in the afterglow region in addition to the N 2 -derived active species such as N atoms and excited N 2 species. The XPS results revealed that such changes in the type and densities of active species in the afterglows can significantly enhance the surface nitriding performance. The origin for the enhanced surface nitriding is attributed to the efficient removal of surface oxygen atoms by reactive H atoms via the formation of H 2 O to result in an efficient surface uptake of nitrogen. Our results show that the N 2 -H 2 afterglows can be effectively used for a selective surface nitriding of oxide films such as TiO 2 at the relatively low temperature range.
Keywords: Active species; Anatase TiO2; Microwave plasma; N2-H2 afterglow; Surface nitridation; Active species; Anatase TiO 2; Microwave plasma; N 2 -H 2 afterglow; Nitriding; Surface nitridation